The Ability of Disability and Possibilities to Use it in the Process of Social Help: Case Analysis of Integrated Camp for Persons with Mental Disabilities and Street Youth - Seniutis, Miroslavas; Petružytė, Donata (Socialinė teorija, empirija, politika ir praktika, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian]The aim of this paper was to discuss experiences of combination of different groups of clients in social help area. Research is orientated to revelation of mutual benefit of interpersonal interactions between persons with mental disabilities and street youth in regular summer camps, giving particular attention to disclosure of abilities of persons with mental disabilities and to revelation of possibilities to use these abilities in the process of social help. Qualitative research was carried out. There where taken non-structured and semi-structured interviews form persons, who participated in integrated summer camps, where possibility for interactions between persons with mental disabilities and street youth was created. Research participants were workers, volunteers and clients (all of them representing two different organizations). We can conclude that persons with mental disabilities offer such a relationship, in which young people (street youth) Btain feeling of unconditional acceptance. This relationship helps to restore their self worth and enables changes in their asocial behavior, as well as discloses their personal qualities such as sensitiveness, tenderness, attentiveness, openness. Thus persons with mental disabilities have ability to be with other because of the worth which he/she on its own (as opposite to the worth that he/she can create). This ability becomes essential motivating factor for street youth to change behavior. Experience of community life together with persons with mental disability demythises social stereotypes about defective humanness of these people. In contrary, their authenticity becomes gift for those who dare to participate in community life together with them and especially for those who experienced a lot of difficulties in their early social life – street youth
Keywords: persons with mental disabilities, street youth, combination of different groups of clients in social help process